Internet of Things and Personalized Healthcare Systems - Krishna, P. Venkata; Gurumoorthy, Sasikumar; Obaidat, Mohammad S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the issues and challenges in personalised healthcare systems. The individual chapters address different aspects of such systems, including the novel Internet of Things (IoT) system architectures in healthcare and emerging e-health based IoT applications. Moreover, the book investigates the impact of cutting-edge innovations on the IoT.
1.IoT and e- health -- 2.Trust in Personalized Medicine -- 3.Big Data and Online Social Networks for Preventive Healthcare -- 4.Privacy in Personalised Healthcare Applications -- 5.Online Social Networks And Healthcare -- 6.Body Area Networks and Personalised Healthcare Applications -- Mobile Cloud and Personalised Healthcare Applications -- 7.Protocols, Algorithms, Architectures for IoT based Personalised Healthcare Applications -- 8.Data mining of health data.
Keywords: Computational intelligence; Big data; Medical informatics; Neural networks (Computer science) .; Biotechnology; Application software; Computational Intelligence; Big Data; Health Informatics; Mathematical Models of Cognitive Processes and Neural Networks; Biotechnology; Computer and Information Systems Applications